Change in plasma cryptococcal antigen titers in Uganda among outpatients with advanced HIV disease from 2017 to 2022 with rollout of national cryptococcal screening - Alexandra Poeschla; Abduljewad Wele; Elizabeth Nalintya; Biyue Dai; David B. Meya; David R. Boulware; Radha Rajasingham (PLoS ONE, 2026)
Introduction Cryptococcal meningitis causes an estimated 19% of AIDS-related deaths globally and is the leading cause of meningitis in adults with HIV. Subclinical infection with cryptococcal antigen (CrAg) is detectable in plasma, and CrAg titer of>=1:160 is predictive of meningitis or death. We evaluated if plasma CrAg titer changed over time in Uganda with the expansion of national CrAg screening programs and antiretroviral (ART) access. Methods We prospectively screened adults with advanced HIV disease (CD4 ≤ 200 cells/μl) for CrAg from 2017 through 2022 using the lateral flow assay and assessed median plasma CrAg titer. Results From November 2017 to May 2022, 436 adults with advanced HIV disease had a positive plasma CrAg test. The median CD4 + cell count was 45 [IQR: 21,94] cells/µL, and median plasma CrAg titer was 1:80 [IQR: 10,1280]. Analysis of median quarterly CrAg titer from 2017–2022 demonstrated a non-statistically significant positive trend in CrAg titer (tau = 0.385, p = 0.086). There was a statistically significant decline in the percentage of participants taking ART at the time of screening (p < 0.001), with 58% reporting never having taken ART in 2022. Conclusions Despite expansion of CrAg screening and ART, median annual CrAg titers have not decreased between 2017 and 2022 in Uganda. Contrary to national reporting of expanded access to ART, our study population had higher rates of ART-naïve status over time, suggesting ongoing late presentation to care for people with advanced HIV disease. In addition, the presence of ART-experienced patients in our study population suggests challenges with treatment adherence and retention. Cryptococcosis persists, and despite public health efforts, people are not presenting to care earlier in their disease course. Continued refinement of CrAg screening programs is needed to reduce AIDS-related deaths.